ETL patterns on YAWL: towards to the specification of platform-independent data warehousing populating processes - Oliveira, Bruno (2014)
The implementation of data warehouse populating processes (ETL) is considered a complex task, not only in terms of the amount of data processed but also in the complexity of the tasks involved. The implementation and maintenance of such processes faces various design drawbacks, such as the change of business requirements, which consequently leads to adapting existing data structures and reusing existing parts of ETL system. We consider that a more abstract view of the ETL processes and its data structures is need as well as a more effective mapping to real execution primitives, providing its validation before conducting an ETL solution to its final implementation. With this work we propose the use of standard solutions, which already has proven very useful in software developing, for the implementation of standard ETL processes. In this paper we approach ETL modelling in a new perspective, using YAWL, a Workflow language, as the mean to get ETL models platform-independent.